BLOOD PRESSURE LOWERING TREATMENT FOR PREVENTION OF CARDIOVASCULAR EVENTS IN PATIENTS WITH ATRIAL FIBRILLATION: AN INDIVIDUAL-PARTICIPANT DATA META-ANALYSIS. (April 2021) - Pinho-Gomes, Ana Catarina Pin; Azevedo, Luis; Copland, Emma; Canoy, Dexter; Nazarzadeh, Milad; Ramakrishnan, Rema; Berge, Eivind; Sundstrom, Johan; Kotecha, Dipak; Woodward, Mark; Rahimi, Kazem
Abstract : Objective: Randomised evidence showing that pharmacological blood pressure (BP) lowering can reduce cardiovascular risk in patients with atrial fibrillation (AF) is limited. Therefore, this study aimed to compare the effect of BP-lowering treatment on fatal and non-fatal cardiovascular outcomes in patients with and without AF. Design and method: We extracted individual participant data from all trials with over 1, 000 person-years of follow-up that had randomly assigned patients to different classes of BP-lowering drugs, BP-lowering drugs vs placebo, or to more vs less intensive BP-lowering regimens. We investigated the effects of BP-lowering treatment on a composite endpoint of major cardiovascular events (stroke, ischaemic heart disease or heart failure) according to AF status at baseline using fixed-effect one-stage individual participant data meta-analyses based on Cox proportional hazards models stratified by trial. Results: Twenty-two trials were included with 188, 570 patients, of whom 13, 266 (7%) had AF at baseline. Patients with AF had lower BP at baseline than patients without AF (143/84 mmHg, SD 21/12mmHg) versus 155/88 mmHg, SD 21/13 mmHg, respectively). Meta-regression showed that relative risk reductions were proportional to trial-level intensity of BP lowering, both in patients with and without AF. The hazard ratio for major cardiovascular events was 0.91 in patients with AF (95% confidence interval [0.83 – 1.00]) and 0.91 without AF (95% confidence interval [0.88 – 0.93]) for each 5-mmHg reduction in systolic BP, with no difference between subgroups (p = 0.91) (Figure). Similar patterns were observed for individual components of the composite primary outcome. In patients with AF, there was no evidence that treatment effects varied according to baseline systolic BP or use of specific drug classes. Figure. No caption available. Conclusions: BP-lowering treatment reduces the risk of major cardiovascular events in patients with AF to a similar extent to that of patients without AF, even when baseline BP is below recommended treatment thresholds. Owing to their higher absolute cardiovascular risk, treatment in patients with AF is likely to result in greater absolute risk reduction than in patients without AF. Guidelines should be updated to clearly recommend pharmacological BP lowering for prevention of cardiovascular events in patients with AF.